Depleted mantle sources through time: Evidence from Lu–Hf and Sm–Nd isotope systematics of Archean komatiites - Blichert-Toft J.; Puchtel I.S. (My University, 2010)
n this study, we present Lu–Hf isotope systematics and Lu and Hf abundances for komatiites from the lowermost part of the 2.8 Ga Kostomuksha greenstone belt in the Baltic Shield and compare these, as well as available Sm–Nd isotope data, with those for the best characterized Archean komatiite systems. The Lu–Hf isotope compositions of four spatially associated differentiated lava ﬂows from the Kostomuksha greenstone belt yield an isochron (MSWD=1.6) with an age of 2931±300 Ma, which represents the ﬁrst Lu–Hf isochron obtained for a suite of co-magmatic komatiite lavas. The calculated mean initial 176Hf/177Hf for the Kostomuksha komatiite samples is 0.281107±3 (2σmean), which corresponds to an initial ε176Hf of +4.9±0.1 (2σmean). Assuming that mantle differentiation occurred 10 Ma after Earth's accretion at 4.558 Ga, this precise initial ratio requires a time-integrated 176Lu/177Hf=0.03759±8, which is identical to the average time-integrated 176Lu/177Hf=0.0375±6 calculated for the best characterized late Archean komatiite systems. Together with the calculated average time-integrated 147Sm/144Nd=0.2091±4 for the same late Archean komatiite systems, these parameters represent our best estimate of the Lu/Hf and Sm/Nd properties in the late Archean mantle and indicate derivation of komatiite magmas from around the globe from long-term melt-depleted sources that were remarkably homogenous in terms of lithophile trace element systematics. These time-integrated ratios are identical to the respective values of 0.0375 and 0.209 calculated by Boyet and Carlson (2006) for the so-called Early Depleted Reservoir (EDR), and may indicate that the late Archean mantle was similar in composition to the putative EDR, whereas early Archean systems had higher, and Proterozoic systems lower time-integrated Lu/Hf and Sm/Nd ratios. The observed decrease in time-integrated Lu/Hf and Sm/Nd in komatiite sources over time is interpreted as strong evidence for the existence of a hidden enriched reservoir complementary to the EDR that has been gradually mixed back into the mantle over time. The overall depletion of the early mantle likely occurred very early in Earth's history as a result of either global magma ocean differentiation or extraction and subsequent long-term isolation of primordial terrestrial crust.
Keywords: Lu–Hf chronology; lithophile trace elements; Archean komatiites; mantle plumes; primordial magma ocean; majorite garnet; Early Depleted Reservoir; hidden enriched reservoir; Докембрий::Архей; Precambrian::Archean